2006
DOI: 10.1111/j.1467-9221.2007.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Religious and National Identity after the Belfast Good Friday Agreement

Abstract: National and religious identification processes can be seen as the basis of the conflict in Northern Ireland, and over the course of the conflict preferred social and political identities became increasingly oppositional and entrenched. This paper reviews this evidence using population-level studies of self-categorized national and religious identity. In an attempt to explore the bases of these identities, two interrelated qualitative studies examining the constructions of national and religious identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 30 publications
3
82
0
1
Order By: Relevance
“…In contrast, there is less consistency surrounding the meaning of British identity (favoured by Protestants), which is typically represented as pertaining to British symbolism. This finding corresponds with earlier research on religious and national identity that suggests, for Protestants, the British identity is associated with greater ambiguity compared with the Irish identity for Catholics (Muldoon et al, 2007). Irrespective of this difference, for both groups, identification is coupled with high levels of interactional and affective commitment.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast, there is less consistency surrounding the meaning of British identity (favoured by Protestants), which is typically represented as pertaining to British symbolism. This finding corresponds with earlier research on religious and national identity that suggests, for Protestants, the British identity is associated with greater ambiguity compared with the Irish identity for Catholics (Muldoon et al, 2007). Irrespective of this difference, for both groups, identification is coupled with high levels of interactional and affective commitment.…”
Section: Resultssupporting
confidence: 88%
“…This is something that has also been picked up by Cassidy and Trew (2004) who have argued that for Protestants, national identity is lower in salience compared with Catholic identity (Cassidy & Trew, 2004). So whilst it was argued earlier that the 'Northern Irish', identity category can present an alternative to traditional oppositional identities (Muldoon et al, 2007) our data suggested that the Northern Irish identity appears to be associated with the same sense of insecurity and alienation among…”
Section: Content and Meaningsupporting
confidence: 69%
See 2 more Smart Citations
“…This paper is concerned with adolescents growing up in Ireland where the division between Catholics and Protestants has provided one of the major fault lines in the society. The high degree of overlap between religion and nationality in Northern Ireland has been associated with the development and maintenance of oppositional ethnonational identities (Muldoon, Trew, Todd, Rougier, & McLaughlin, 2007). Personal experiences and characteristics are seen to impact on the nature and strength of ethnonational identities, but the nature of these identities also varies with changes in intergroup relations over time and locality.…”
mentioning
confidence: 99%